Monetary incentives at retrieval promote recognition of involuntarily learned emotional information. Issue 4 (7th March 2018) - Yan, Chunping; Li, Yunyun; Zhang, Qin; Cui, Lixia
Abstract : Previous studies have suggested that the effects of reward on memory processes are affected by certain factors, but it remains unclear whether the effects of reward at retrieval on recognition processes are influenced by emotion. The event-related potential was used to investigate the combined effect of reward and emotion on memory retrieval and its neural mechanism. The behavioral results indicated that the reward at retrieval improved recognition performance under positive and negative emotional conditions. The event-related potential results indicated that there were significant interactions between the reward and emotion in the average amplitude during recognition, and the significant reward effects from the frontal to parietal brain areas appeared at 130–800 ms for positive pictures and at 190–800 ms for negative pictures, but there were no significant reward effects of neutral pictures; the reward effect of positive items appeared relatively earlier, starting at 130 ms, and that of negative pictures began at 190 ms. These results indicate that monetary incentives at retrieval promote recognition of involuntarily learned emotional information.